Ensuring The Economic Security of The Industrial Complex - Yuri KOSTYUKHIN; Svetlana ULYANOVA; Еvgenia N. ELISEEVA; Daria SAVINOVA (Communications of International Proceedings, 2022)
The system of economic security of the enterprise includes a set of the following structural elements: security policy and strategy, scientific theory of security, security provisions, means and methods of security implementation. The concept consisting of the goal of the complex system of ensuring economic security of the enterprise, its objectives, principles of activity, object and subject, as well as strategic and tactical approaches has been proposed as the basis for the creation of an integrated system of economic security of the enterprise. The article considers threats to security objects, which come from external and internal sources of danger, set the content of external and internal security activity. It also proposes a new approach to ensuring economic security in the industrial sector in conditions of economic transformation and the actualization of the issue of innovation activity.
Keywords: Industrial complex; economic security; system of analysis; innovation attractiveness; methodology.